Hepatitis B and skin: review - Zonunsanga (Our Dermatology Online, 2015)
Hepatitis B virus (HBV) infection and its complications have become a global health problem. The spectrum of HBV infection ranges from asymptomatic carrier state to chronic hepatitis. It is usually preceded by constitutional symptoms. It has a wide range of dermatological manifestations. This review includes the pathogenesis along with the pathophysiology with their clinical significance and overview of the treatment.